Differential manifestation of COVID-19 anxiety and adherence to precautionary measures as a function of socioeconomic status: A longitudinal study in coastal Andhra Pradesh - Pradeep Kandikatla; Roopa Reddy Pandraveti; Vikramsimha Bommireddy; Raghudeep Darisi; Anudeep Kapalavayi; Srikanth Reddy Karra (Journal of Primary Care Specialties, 2021)
Introduction: There is a possibility that the coronavirus disease (COVID-19)-related anxiety may differ between people from varied socioeconomic status for a variety of reasons. Furthermore, the adherence to COVID-19 precautionary measures could be different between socioeconomic strata in light of the differences in opportunities to more effectively follow these measures for people from different socioeconomic status. Aim and Objectives: The aim of this study was to check the differences in COVID-19 anxiety and precautionary measure adherence between subjects from different socioeconomic strata and to conduct a stratified analysis of the association between anxiety and adherence based on socioeconomic status of the participants. Materials and Methods: This longitudinal study was conducted in the months of July and November 2020 among 648 subjects belonging to the coastal districts of Andhra Pradesh. The COVID-19 Anxiety Scale (CAS) was used to assess the disease-related anxiety among the study participants, and self-reported adherence (SRA) scores were collected to document the adherence of the study subjects to COVID-19 precautionary measures. Statistical analysis was performed using SPSS version 20 software. Results: Significant differences were found in the CAS scores between subjects from different socioeconomic strata in the month of July, while no such observations were made in November. For the outcome of SRA scores, there were significant differences between socioeconomic strata at both the study time points. Overall, the mean CAS and SRA scores decreased from July (20.35 ± 5.54 and 14.48 ± 3.45, respectively) to November (15.96 ± 5.67 and 12.57 ± 4.17, respectively). Conclusion: The study results highlight the need to reinforce the necessity and importance of adhering to COVID-19 precautionary measures in light of the potential danger of the second wave of COVID-19 in the country.